2019
DOI: 10.3847/1538-4357/ab3d2d
|View full text |Cite
|
Sign up to set email alerts
|

Linear Acoustic Waves in a Nonisothermal Atmosphere. II. Photospheric Resonator Model of Three-minute Umbral Oscillations

Abstract: The velocity oscillations observed in the chromosphere of sunspot umbrae resemble a resonance in that their power spectra are sharply peaked around a period of about three minutes. In order to describe the resonance that leads to the observed 3-minute oscillations, we propose the photospheric resonator model of acoustic waves in the solar atmosphere. The acoustic waves are driven by the motion of a piston at the lower boundary, and propagate in a nonisothermal atmosphere that consists of the lower layer (photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…So, the threeminute oscillation at the sunspot umbra could come from the upper photosphere or the temperature minimum region and then propagate to the chromosphere, supporting the interpretation that propagating waves above the sunspots originate from the lower solar atmosphere (De Moortel et al 2002;O'Shea et al 2002;Brynildsen et al 2004;Khomenko & Collados 2015;Krishna Prasad et al 2015). In other words, the three-minute oscillation can be regarded as the upwardly propagating slow magnetoacoustic waves (e.g., Su et al 2016;Chae et al 2019;Cho & Chae 2020;Feng et al 2020b). Finally, Chae et al (2017) found that the threeminute oscillation in the light bridge or umbral dots of a sunspot originates from the photosphere (see aslo Cho et al 2019), which is consistent with our results and further suggests that the CYRA data is reliable.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…So, the threeminute oscillation at the sunspot umbra could come from the upper photosphere or the temperature minimum region and then propagate to the chromosphere, supporting the interpretation that propagating waves above the sunspots originate from the lower solar atmosphere (De Moortel et al 2002;O'Shea et al 2002;Brynildsen et al 2004;Khomenko & Collados 2015;Krishna Prasad et al 2015). In other words, the three-minute oscillation can be regarded as the upwardly propagating slow magnetoacoustic waves (e.g., Su et al 2016;Chae et al 2019;Cho & Chae 2020;Feng et al 2020b). Finally, Chae et al (2017) found that the threeminute oscillation in the light bridge or umbral dots of a sunspot originates from the photosphere (see aslo Cho et al 2019), which is consistent with our results and further suggests that the CYRA data is reliable.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…They are thought to be resonant modes of sunspot oscillations, with cavities that may be located at sunspot umbrae in the solar layers of sub-photospheres (Scheuer & Thomas 1981;Thomas 1984Thomas , 1985 or chromospheres (Uexkuell et al 1983;Gurman 1987;Khomenko & Collados 2015). The typical three-minute oscillation above the sunspot can be simultaneously detected from the photosphere through the chromosphere and transition region to the corona, supporting the interpretation of propagating waves at sunspots (De Moortel et al 2002;O'Shea et al 2002;Brynildsen et al 2004;Su et al 2016;Chae et al 2019), for instance trans-sunspot waves (Tziotziou et al 2006) or slow magnetoacoustic waves (Bloomfield et al 2007;Krishna Prasad et al 2015;Wang et al 2018;Cho et al 2019;Cho & Chae 2020).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the last years several works have pointed out the relevance of resonances in the umbral chromosphere (Botha et al 2011;Snow et al 2015;Felipe 2019) and photosphere (Chae et al 2019). Recently, Jess et al (2020a) claimed the presence of a resonant cavity above a sunspot based on the detection of a high-frequency power peak in He i 10830 Å observations.…”
Section: Introductionmentioning
confidence: 99%
“…They show an enhanced power and a shorter dominant period, from waves with an amplitude of a few hundred meters per second in the five-minute band at the photosphere, to amplitudes of several kilometers per second in the three-minute band at the chromosphere. Various models have been proposed to explain this behaviour [1][2][3] , including the presence of a chromospheric resonance cavity between the photosphere and the transition region [4][5][6][7][8] . Jess et al 9 claimed the detection of observational evidence supporting this model, obtained from the comparison of spectropolarimetric observations and numerical simulations.…”
mentioning
confidence: 99%